2016
DOI: 10.1093/schbul/sbw005
|View full text |Cite
|
Sign up to set email alerts
|

Disturbances in Response Inhibition and Emotional Processing as Potential Pathways to Violence in Schizophrenia: A High-Density Event-Related Potential Study

Abstract: Objective: Increased susceptibility to emotional triggers and poor response inhibition are important in the etiology of violence in schizophrenia. Our goal was to evaluate abnormalities in neurophysiological mechanisms underlying response inhibition and emotional processing in violent patients with schizophrenia (VS) and 3 different comparison groups: nonviolent patients (NV), healthy controls (HC) and nonpsychotic violent subjects (NPV). Methods: We recorded high-density Event-Related Potentials (ERPs) and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 48 publications
(58 reference statements)
2
25
0
1
Order By: Relevance
“…All participants, as reported in our previous studies using the same participants [29, 38], had no significant co-morbid medical, psychiatric, or neurological illnesses. Participants with any history of drug or alcohol dependence were excluded, along with any recent drug or alcohol abuse occurring 6 months or less to their participation in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants, as reported in our previous studies using the same participants [29, 38], had no significant co-morbid medical, psychiatric, or neurological illnesses. Participants with any history of drug or alcohol dependence were excluded, along with any recent drug or alcohol abuse occurring 6 months or less to their participation in the study.…”
Section: Methodsmentioning
confidence: 99%
“…To be included in the non-violent group, there could be no evidence of a physical assault within the past year, or any lifetime episodes of severe physical aggression, accompanied with a score ≤ 15 on the LHA, and ≤ 2 on the PA-people. This study used the same inclusion and exclusion criteria found in our previous studies [29, 38]. …”
Section: Methodsmentioning
confidence: 99%
“…During the EEG response inhibition task, consistent with what was observed in the D-KEFS and CPT measures, both the 22q11.2DS and the schizophrenia groups displayed poorer d-prime scores and longer reaction times compared to their neurotypical peers. In schizophrenia, lower d-prime scores (Groom et al, 2008;Simmonite, Bates, Groom, Hollis, & Liddle, 2015) and longer reaction times (Birkett et al, 2007;Krakowski et al, 2016) have been previously reported in the context of Go/No-Go tasks.…”
Section: Discussionmentioning
confidence: 52%
“…Very little is likewise known about response inhibition at prodromal and early stages of schizophrenia, though those individuals seem to show slowed and variable motor responses and decreased engagement of regions implicated in inhibitory control (Fryer et al, 2018). In contrast, behavioral (Badcock, Michie, Johnson, & Combrinck, 2002;Bellgrove et al, 2006;De Sanctis et al, 2012;Enticott, Ogloff, & Bradshaw, 2008;Lipszyc & Schachar, 2010), electrophysiological (EEG) (Chun et al, 2013;Ford et al, 2004;Hughes, Fulham, Johnston, & Michie, 2012;Kiehl, Smith, Hare, & Liddle, 2000;Krakowski et al, 2016;Weisbrod, Kiefer, Marzinzik, & Spitzer, 2000), and fMRI techniques (Ford et al, 2004;Hughes et al, 2012;Kaladjian et al, 2007;Rubia et al, 2001) reveal clear differences in inhibitory processes in chronic schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…The immune system may influence neurometabolic, neuroendocrine, neurodevelopmental processes ( 32 , 33 ), especially the effect of T-cell on cognitive function ( 34 ), learning and memory ( 35 ), social behavior ( 36 ), which are all critical etiological pathways for schizophrenia. Compared to non-violent patients, violent schizophrenic patients show disturbances in response inhibition and emotional processing ( 37 ), impaired neurocognition ( 38 , 39 ), and stronger neurodevelopmental symptoms ( 40 ). Therefore, in the current study, high-throughput sequencing technology was used to analyze the characteristics and diversity of immune molecules to explore the role of T cells in the immune system-induced pathogenesis of schizophrenia.…”
Section: Introductionmentioning
confidence: 99%